Service Quality and Brand Image Impact on Consumer Satisfaction on Ticket Purchasing in the KAI Access Application - Francis Tantri; Marlina Iryatie; Intan Permata Sari; A Afilah (Whoosh: Journal of Transportation and Logistic, 2026)
Developments in technology have grown more advanced. Presently, sales have been conducted not only through conventional or offline marketing but also through online marketing systems. Therefore, competition in the transportation service business sector has become more intense, which requires companies to maintain their quality to build a good reputation in order to compete in this business sector. The purpose of this research was to examine the impact of service quality and brand image partially and simultaneously on KAI Access consumer satisfaction. Descriptive quantitative methods were used in this research. This research findings show that, 1) service quality has a partial positive impact on KAI Access’ consumer satisfaction, 2) brand image has a partial positive impact on KAI Access’ consumer satisfaction, and 3) service quality and brand image simultaneously impact KAI Access’ consumer satisfaction.